Experience in the management of the true ankylosis of the temporomandibular joint: A suggested protocol for treatment - Al-Kamali, Reiadh K.; Al-Zubaidi, Ali F.; Ali, Hundreen M. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: True ankylosis of the temporomandibular joint may be defined as joint surfaces fusion. It can affect the function adversely and when occurs during childhood, it can adversely affect mandibular growth. The treatment is usually surgical, but, unfortunately, poses a significant challenge because of the high recurrence rate. The objective of this paper is to evaluate the outcome of following a definitive protocol in the treatment of temporomandibular joint ankylosis.Methods: Seventy-seven patients, 36 unilateral and 41 bilateral ankylosis (118 ankylosed joints) were diagnosed clinically and radiologically as having true ankylosis of the temporomandibular joint during the period between 2001 and 2013. Resection of the ankylosed bone or horizontal ramus osteoctomy of the affected side with interpositional autogenic or alloplastic material, with possible ipsilateral and/or contralateral coronoidectomy to achieve the definitive interincisal opening of not less than 35mm.Results: The postoperative measurement of interincisal opening of ≥35mm with lateral and protrusive movement was the criteria for success of surgery. Reankylosis occurred in 7 unilateral and 12 bilateral cases.Conclusion: Postoperative jaw opening exercises are crucial for lasting success and failure of patient compliance is the cause of reankylosis.